2015
DOI: 10.1111/tct.12357
|View full text |Cite
|
Sign up to set email alerts
|

Early experience of a virtual journal club

Abstract: This novel VJC model is a feasible and popular method of delivering a journal club in the postgraduate setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“… 23 , 52 , 56 This curated commentary may also be submitted and published as an article commentary or letter to the editor. 67 Disadvantages of Twitter include character limits and lack of an underlying organizational structure, making delayed asynchronous engagement more challenging. 52 , 54 , 64 Furthermore, many educators and learners do not use Twitter as consumers, or feel comfortable engaging in Twitter conversations as participants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 23 , 52 , 56 This curated commentary may also be submitted and published as an article commentary or letter to the editor. 67 Disadvantages of Twitter include character limits and lack of an underlying organizational structure, making delayed asynchronous engagement more challenging. 52 , 54 , 64 Furthermore, many educators and learners do not use Twitter as consumers, or feel comfortable engaging in Twitter conversations as participants.…”
Section: Introductionmentioning
confidence: 99%
“…One study of general surgery residents found that an online journal club using a combination of email, Facebook, and Twitter was very well received by learners, noting that it was easy to participate in, helpful in keeping up with the latest literature, and valuable for developing critical appraisal skills. 67 Learners found it significantly preferable to traditional journal club, and the authors noted that the online journal club led to the successful publication of eight article commentaries. 67 Similar data were found by several other authors, noting improved learner satisfaction; 25 , 57 , 61 however, more data are needed on higher level learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…11 Some virtual journal clubs have presented no analytic data, focusing their discussion on the content of the online discourse. 22 In studies presenting analytics, page views of published online journal clubs have ranged from 370 in a month 23 to 1324 in 2 weeks. 10 Analytics at their best are an inadequate and variable proxy for impact.…”
Section: Discussionmentioning
confidence: 99%
“…Aggregate Analytic Data for the First 14 Days of JGME-ALiEM Hot Topics in Medical Education Discussion Using Various Social Media Platforms (January[11][12][13][14][15][16][17][18][19][20][21][22][23][24] 2016) …”
mentioning
confidence: 99%
“…We regularly publish articles describing new technologies. In this issue, for example, you can read about iPads being provided to third‐year medical students for use during clinical rotations, a virtual journal club using e–mail and social media, and smartphones being used as laparoscopic trainers …”
mentioning
confidence: 99%